The effect of plasmon resonance coupling in P3HT-coated silver nanodisk monolayers on their optical sensitivity. Issue 41 (7th October 2016) - Geldmeier, Jeffrey A.; Mahmoud, Mahmoud A.; Jeon, Ju-Won; El-Sayed, Mostafa; Tsukruk, Vladimir V.
Abstract : The correlation of the Langmuir Blodgett deposition phase with the reversible LSPR modulation of P3HT-coated silver nanodisk monolayers. Abstract : We report on the optical properties of silver nanodisk (Ag ND) Langmuir Blodgett monolayers that were transferred to substrates in different coupling regimes. Ag ND monolayers deposited in the liquid expanded–gaseous (Le–G) phase demonstrated individual plasmon resonance behavior while monolayers deposited in the liquid condensed–liquid expanded (Lc–Le) and solid–liquid condensed (S–Lc) phases exhibited plasmon coupling between closely packed adjacent nanoparticles, which caused a red shift in their localized surface plasmon resonance (LSPR) spectra. The initial presence of excess polyvinylpyrrolidone (PVP) surfactant micelles on the Ag ND monolayers could be eliminated by first compressing the monolayers to high surface pressures, resulting in blue shifted extinction spectra and increased sensitivity as micelles depleted into the subphase. Ag ND monolayers were then used in conjunction with a conjugated poly(3-hexylthiophene-2, 5-diyl) (P3HT) medium to reversibly modulate the LSPR by changing the local refractive index around the nanoparticles. Ultimately, a high reversible LSPR shift of 27 nm was observed with an applied electropotential of ±500 mV to the P3HT-coated Ag ND monolayer. A high refractive index sensitivity (RIS) of 141 nm per RIU was found for monolayers deposited in the Lc–Le phase due to an increase in hot spot formation.